Awareness and Attitude Towards Breast Cancer Prevention Among Hostel Workers in Kabardino-Balkaria State University - Hardinas Anwar, Musdaliva; Mersha Ashagre, Saron (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Breast cancer is the most frequent type of cancer in women and it was estimated that 2.3 million new breast cancer cases were diagnosed in 2020 (24% of all cancers); it ranks second overall (10.9% of all cancers). To asses awareness and attitude for prevention of breast cancer in the field of research. Source of the population were all reproductive age women workers in university hostels. Study group consisted of all women of reproductive age (40–65 years) who had there is a chance to be randomly selected from the hostels, Community based cross-sectional study were carried out by using well-structured questioner. Many of the participants were not knowledgeable about breast cancer. Women older than 50 years of age are at higher risk, yet only 10 (12.5) respondents had good awareness, that is, they scored is greater than or equal to the mean. Twenty-six (32.5%) participants have no idea had factors that increase the likelihood of developing breast cancer. Similarly, twenty-one (26.3%) of participants confirmed that they had no information about the symptoms of breast cancer. More than three-fourths of the participants (85 %) disagreed with that screening helps in prevention of carcinoma of the breast..